2014
DOI: 10.1016/j.procs.2014.05.159
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards Automated Kepler Scientific Workflows for Computer-aided Drug Discovery and Molecular Simulations

Abstract: We describe the development of automated workflows that support computed-aided drug discovery (CADD) and molecular dynamics (MD) simulations and are included as part of the National Biomedical Computational Resource (NBCR). The main workflow components include: file-management tasks, ligand force field parameterization, receptor-ligand molecular dynamics (MD) simulations, job submission and monitoring on relevant high-performance computing (HPC) resources, receptor structural clustering, virtual screening (VS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Due to the countless options available in the configuration file of MD software reproducibility has been a key issue in MD simulations. Workflow management, already available as a tool external to MD software 59 , offers a solution by keeping a log of all steps taken. QwikMD, while guiding the user interactively through the process of preparing, running and analyzing MD simulations, keeps track of every single step by writing two files, a .qwikMD file and a .infoMD file.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the countless options available in the configuration file of MD software reproducibility has been a key issue in MD simulations. Workflow management, already available as a tool external to MD software 59 , offers a solution by keeping a log of all steps taken. QwikMD, while guiding the user interactively through the process of preparing, running and analyzing MD simulations, keeps track of every single step by writing two files, a .qwikMD file and a .infoMD file.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, molecular simulation, which is based on investigation of the binding interaction mechanism of a biomacromolecule with small molecules, plays an important role in the discovery and development of drugs . In this work, molecular dockings between lovastatin and four B‐DNA fragments were performed using Autodock 4.2 to further clarify the binding mode of lovastatin with B‐DNA and to obtain information about the interaction forces.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is practical and warranted in settings where the goal is to screen large libraries of potential drug compounds [ 189 191 ]. An extensive review of the unique challenges in these settings can be found in [ 163 , 192 ].…”
Section: Recent Applications Made Possible By Hardware and Algorithmimentioning
confidence: 99%